2021
DOI: 10.1038/s41598-021-92122-1
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of crude oil by immobilized Exiguobacterium sp. AO-11 and shelf life evaluation

Abstract: Exiguobacterium sp. AO-11 was immobilized on bio-cord at 109 CFU g−1 carrier for the removal of crude oil from marine environments. To prepare a ready-to-use bioremediation product, the shelf life of the immobilized cells was calculated. Approximately 90% of 0.25% (v/v) crude oil removal was achieved within 9 days when the starved state of immobilized cells was used. The oil removal activity of the immobilized cells was maintained in the presence of oil dispersant (89%) and at pH values of 7–9. Meanwhile, pH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 57 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…6 c). Similarly, in a recent study, the starvation state of cells was obtained after prolonged storage, resulting in faster hydrocarbon biodegradation than with fresh cells 47 . Furthermore, the biobooms preserved in SM at RT for 100 days was still active and provided the highest crude oil biodegradation (85.2 ± 2.3%) in CFMM at 3 days (Fig.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…6 c). Similarly, in a recent study, the starvation state of cells was obtained after prolonged storage, resulting in faster hydrocarbon biodegradation than with fresh cells 47 . Furthermore, the biobooms preserved in SM at RT for 100 days was still active and provided the highest crude oil biodegradation (85.2 ± 2.3%) in CFMM at 3 days (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…The immobilized cells were enumerated daily for 5 days as described by Naloka et al 12 . The morphology of the immobilized cells was visualized by scanning electron microscopy (SEM) using a JSM-IT500HR model (JEOL Ltd., Tokyo, Japan) according to Sakdapetsiri et al 47 .…”
Section: Methodsmentioning
confidence: 99%
“…According to the findings, it was established that aldehyde fibers have the most favorable immobilization environment for the different bacterial species as well as biodegradation of crude oil. [111] Another study was carried out by Sakdapetsiri et al [112] in which they immobilized Exiguobacterium sp on different polymeric materials that included polyurethane foam, polypropylene nanofibers, and aqua-porous gel for biodegradation of crude oil. Similarly, their findings proved the efficiency of immobilized vs un-immobilized cells in the degradation of crude oil.…”
Section: Nanofibers and Bacteria Immobilization In Crude Oil Treatmentmentioning
confidence: 99%
“…Immobilized cells were able to remove nearly 90 % of the oil under study in about 9 days and also they were able to be reused up to five times without significant loss of activity. [112] Partovinia et al [113] reported immobilization of Bacillus licheniformis on polyvinyl alcohol, alginate nanofibers reinforced by halloysite nanotubes (HNTs), and cross-linked with glyoxal (GO) for bioremediation of crude oil. Biodegradation studies revealed a higher performance of immobilized bacteria on nanofiber webs (NC-NFWs) compared to the free cells (85 % and 48 % degradation respectively), as depicted in Figure 8.…”
Section: Nanofibers and Bacteria Immobilization In Crude Oil Treatmentmentioning
confidence: 99%
See 1 more Smart Citation